Kiến thức và thái độ về biện pháp tránh thai của sinh viên năm thứ nhất: Nghiên cứu tại Trường Cao đẳng Bình Thuận - Nguyễn Thị Sáu, Nguyễn Thị Sáu; Đỗ Huy Sơn, Đỗ Huy Sơn; Trần Thị Hữu An, Trần Thị Hữu An; Võ Huyền Diễm Tú Võ Huyền Diễm Tú (Tạp chí Giáo dục, 2026)
Given the limited provision of sexual and reproductive health education in vocational institutions, assessing students’ knowledge and attitudes toward contraceptive methods is important. Knowledge is recognized as a determinant of health-related attitudes and behaviors. This study aimed to assess knowledge and attitudes toward contraceptive methods among firstyear students at Binh Thuan College and to identify factors associated with these outcomes. A cross-sectional study was conducted in 2025 among 420 first-year students using a self-administered structured questionnaire. Descriptive statistics and multivariable logistic regression analysis were applied to examine associated factors. The results revealed that only 14% of students had adequate knowledge and 24.8% demonstrated positive attitudes toward contraceptive methods. Knowledge was significantly associated with age, ethnicity, residence, and academic major (p < 0.05). Students with limited knowledge were 5.2 times more likely to exhibit negative attitudes (95% CI: 2.93-9.35), whereas those living away from their families were less likely to report positive attitudes (OR = 0.52; 95% CI: 0.29-0.95). The findings underscore the importance of strengthening sexual and reproductive health education in vocational training. These findings provide empirical evidence to support the integration of sexual and reproductive health education into vocational curricula. Integrating this content systematically into curricula, alongside school-based counseling and culturally responsive skills education, may enhance awareness and promote safer reproductive health behaviors.